Effect of Providing Moringa Snacks on Underweight Toddler - Yulia Fitri; Putri Santy (Institute of Computer Science (IOCS), 2022)
Malnutrition could resulted disturbance physique and mental illness and risk death . Moringa oleifera is rich in phytonutrients so that Becomes source promising nutrition _ however use in fortification food still limited . The research objective was to determine the effect of giving cake snacks dry moringa against enhancement heavy body toddler underweight . Design used _ is Quasi Experimental with nonrandomized pretest-posttest design. The research sample is 30 toddlers (15 case groups and 15 control groups). Measurement heavy body conducted with digital scales and be measured 2 times ie before intervention and after intervention . Moringa snacks given for 3 weeks Data analysis using the T test. The results of the study showed the provision of cake snacks dry with additions powder Moringa leaves 100 mg per day for 3 week significantly improve heavy body toddler (P=0.00). Moringa can increase the weight of underweight toddlers. Further research is needed regarding the effectiveness of Moringa in overcoming health problems in children in more coverage large including stunting.